2004
DOI: 10.1159/000075619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on the Saturated and Monounsaturated Fatty Acids of the Newborn Rat Cerebellum

Abstract: Caffeine (1,3,7-trimethylxanthine) is one of the most commonly consumed drugs in our daily life, and its use is increasing. However, very little attention has been paid to its potential effects on early growth and development. Because of the steady increase in breast feeding of infants and because caffeine diffuses readily into breast milk, the present study examined if caffeine intake by newborn rats during lactation would affect the saturated and monounsaturated fatty acids in the growing cerebellum. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…High caffeine citrate increased total dendritic length and arborization of layer III pyramidal neurons of the prefrontal cortex at P35 and P70 of newborn rat pups when administrated at P1 to P12 [ 111 ]. Decreased cerebellar weight and increased saturated fatty acid concentration of the cerebellum were detected after caffeine citrate administration to newborn rats for ten postnatal days [ 112 ]. Moderate caffeine administrated to rat pups from P2 until P6 decreased adenosine receptor subtype A1 binding in the molecular layer of cerebellum [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…High caffeine citrate increased total dendritic length and arborization of layer III pyramidal neurons of the prefrontal cortex at P35 and P70 of newborn rat pups when administrated at P1 to P12 [ 111 ]. Decreased cerebellar weight and increased saturated fatty acid concentration of the cerebellum were detected after caffeine citrate administration to newborn rats for ten postnatal days [ 112 ]. Moderate caffeine administrated to rat pups from P2 until P6 decreased adenosine receptor subtype A1 binding in the molecular layer of cerebellum [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other experimental studies have found potential neurotoxicity and behavioral dysfunction following caffeine administration. Studies have documented alterations in astrocytogenesis,27 increased neuronal cell death,9, 28, 29 reduction in proliferating glial cells,3 and decreased weight and altered fatty acid composition in the cerebellum in caffeine‐treated rat and mice pups 30. There have also been reports of behavioral dysfunction including hyperalgesia,4 hypoactivity,31 and impaired spatial learning tasks that persist into adulthood in rats exposed to caffeine within the first week 4.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unknown whether high blood concentrations of caffeine have an impact on neurological prognosis. However, several studies have reported that high blood concentrations of caffeine are detrimental to brain neurons [16][17][18]. Therefore, the results show that patients with high blood concentrations of caffeine require long-term developmental follow-up.…”
Section: Discussionmentioning
confidence: 99%